Species diversity of Asteraceae in Gayo Highlands, Bener Meriah District, Aceh Province, Indonesia - VIVERA RUSELLI PUSPA; ZUMAIDAR ZUMAIDAR; NURDIN NURDIN; FITMAWATI FITMAWATI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Puspa VR, Zumaidar, Nurdin, Fitmawati. 2024. Species diversity of Asteraceae in Gayo Highlands, Bener Meriah District, Aceh Province, Indonesia. Biodiversitas 25: 2828-2837. Asteraceae flourishes in the Gayo Highlands of the Bener Meriah District, Aceh Province, Indonesia despite being frequently overlooked due to its classification as a wild plant. There has been no comprehensive documentation of the non-cultivated Asteraceae species indigenous to this location. Thus, this study endeavored to elucidate the diversity of the Asteraceae species in the Gayo Highlands. Data on Asteraceae diversity were amassed using the quadrat method across eight sub-districts, encompassing abandoned land and roadside areas. The composition of species was scrutinized through the Important Value Index (IVI) and the diversity index was quantified utilizing the Shannon-Wiener index. The results revealed 13 species of Asteraceae comprising a total of 9,780 individual specimens, including Ageratum conyzoides L., Bidens pilosa L., Acmella uliginosa (Sw.) Cass., Crassocephalum crepidioides (Benth.) S. Moore., Galinsoga parviflora Cav., Erigeron sumatrensis Retz., Sonchus oleraceus L., Synedrella nodiflora (L.) Gaertn., Gerbera jamesonii Adlam., Sphagneticola trilobata (L.) Pruski., Emilia sonchifolia (L.), Tridax procumbens L., and Youngia japonica (L.) DC. Ageratum conyzoides registered the highest IVI at 143.91, whilst S. oleraceus had the lowest at 3.53. According to the Shannon-Wiener index, the diversity of the Asteraceae in the Gayo Highlands is denoted as low (?=1.69). This exploration provides contemporary insights into the Asteraceae diversity within the Gayo Highlands, serving as a valuable reference for both researchers and interested stakeholders.